Internal clock and the surgical ICU patient. Issue 2 (April 2020) - Coppola, Silvia; Caccioppola, Alessio; Chiumello, Davide
Abstract : Purpose of review: The alteration of circadian rhythms in the postoperative period has been demonstrated to influence the outcomes. With this narrative review we would revise how anesthesia, surgery and intensive care can interfere with the circadian clock, how this could impact on the postsurgical period and how to limit the disruption of the internal clock. Recent findings: Anesthesia affects the clock in relation to the day-time administration and the type of anesthetics, N-methyl-D-aspartate receptor antagonists or gamma-aminobutyric acid receptors agonists. Surgery causes stress and trauma with consequent alteration in the circadian release of cortisol, cytokines and melatonin. ICU represents a further challenge for the patient internal clock because of sedation, immobility, mechanical ventilation and alarms noise. Summary: The synergic effect of anesthesia, surgery and postoperative intensive care on circadian rhythms require a careful approach to the patient considering a role for therapies and interventions aimed to re-establish the normal circadian rhythms. Over time, approach like the Awakening and Breathing Coordination, Delirium Monitoring and Management, Early Mobility and Family engagement and empowerment bundle can implement the clinical practice.